Modern approaches to correction mineral and bone disorders in kidney transplant recipients - O. N. Vetchinnikova (Вестник трансплантологии и искусственных органов)
The syndrome of mineral and bone disorders in patients with chronic kidney disease after kidney transplantation include hypophosphatemia, hypercalcemia, hypovitaminosis D, and decreased bone mineralization (secondary osteoporosis). The modern strategy of prevention and treatment of post-transplantation mineral and bone disorders is based on the principles of individual approach, taking into account the assessment of risk factors and minimizing the factors that caused these disorders. An attempt to compensate for phosphorus deﬁ ciency is usually ineffective and even dangerous due to complications. This review analyzes different correction´s methods of symptomatic hypercalcemia and hypercalcemia after kidney transplantation secondary to hyperparathyroidism. Also in this review presented modern approaches to the prevention and treatment of posttransplant osteoporosis. Also it shows the effects and indications for use steroid sparing/withdrawal, vitamin D and vitamin D receptor activator, drug and surgical correction of hyperparathyroidism, bisphosphonates and other medications.